X-Ray diffraction and vibrational spectroscopic study of 2-chloro-N-{4-[3-(2,5-dimethylphenyl)-3-methylcyclobutyl]-thiazol-2-yl}-acetamide - Caliskan, Nezihe; Guntepe, Feyizan; Yuksektepe, Cigdem; Cukurovali, Alaaddin; Buyukgungor, Orhan (Pleiades Publishing Inc, 2010)
The title compound C18H21ClN2SO crystallizes with Z = 4 in space group P2(1)/c. The structure of the title compound was characterized by H-1-NMR, C-13-NMR, IR and single crystal diffraction. There are an intermolecular N-HaEuro broken vertical bar O hydrogen bond and a C-HaEuro broken vertical bar pi interactions in crystal packing. In addition to the molecular geometry and packing obtained from X-ray experiment, the molecular geometry and vibrational frequencies of the title compound in ground state have been calculated using density functional theory method DFT (B3LYP) with 6-31G (d, p) basis set. Calculated frequencies, bond lengths, angles and dihedral angles are in good agreement with the corresponding experimental data.
Keywords: X-ray structure determination; DFT calculation; B3LYP; IR spectra; NMR spectra